Functionality after arthroscopic debridement of central triangular fibrocartilage tears with central perforations - Möldner, Meike Anneli; Unglaub, Frank; Hahn, Peter; Müller, Lars Peter; Bruckner, Thomas; Spies, Christian (The journal of hand surgery. [American volume], 2015)
To investigate functional and subjective outcome parameters after arthroscopic debridement of central articular disc lesions (Palmer type 2C) and to correlate these findings with ulna length.Fifty patients (15 men; 35 women; mean age, 47 y) with Palmer type 2C lesions underwent arthroscopic debridement. Nine of these patients (3 men; 6 women; mean static ulnar variance, 2.4 mm; SD, 0.5 mm) later underwent ulnar shortening osteotomy because of persistent pain and had a mean follow-up of 36 months. Mean follow-up was 38 months for patients with debridement only (mean static ulnar variance, 0.5 mm; SD, 1.2 mm). Examination parameters included range of motion, grip and pinch strengths, pain (visual analog scale), and functional outcome scores (Modified Mayo Wrist score [MMWS] and Disabilities of the Arm, Shoulder, and Hand [DASH] questionnaire).Patients who had debridement only reached a DASH questionnaire score of 18 and an MMWS of 89 with significant pain reduction from 7.6 to 2.0 on the visual analog scale. Patients with additional ulnar shortening reached a DASH questionnaire score of 18 and an MMWS of 88, with significant pain reduction from 7.4 to 2.5. Neither surgical treatment compromised grip and pinch strength in comparison with the contralateral side. We identified 1.8 mm or more of positive ulnar variance as an indication for early ulnar shortening in the case of persistent ulnar-sided wrist pain after arthroscopic debridement.Arthroscopic debridement was a sufficient and reliable treatment option for the majority of patients with Palmer type 2C lesions. Because reliable predictors of the necessity for ulnar shortening are lacking, we recommend arthroscopic debridement as a first-line treatment for all triangular fibrocartilage 2C lesions, and, in the presence of persistent ulnar-sided wrist pain, ulnar shortening osteotomy after an interval of 6 months. Ulnar shortening proved to be sufficient and safe for these patients. Patients with persistent ulnar-sided wrist pain after debridement who had preoperative static positive ulnar variance of 1.8 mm or more may be treated by ulnar shortening earlier in order to spare them prolonged symptoms.Therapeutic IV.